A consistent second‐order hydrodynamic model in the time domain for floating structures with large horizontal motions. (29th October 2021) - Shao, Yanlin; Zheng, Zhiping; Liang, Hui; Chen, Jikang
Abstract: Floating offshore structures often exhibit low‐frequency oscillatory motions in the horizontal plane, with amplitudes in the same order as their characteristic dimensions and larger than the corresponding wave‐frequency responses, making the traditional formulations in an inertial coordinate system inconsistent and less applicable. To address this issue, we extend and explore an alternative formulation completely based on a non‐inertial body‐fixed coordinate system. Unlike the traditional seakeeping models, this formulation consistently allows for large‐amplitude horizontal motions. A numerical model based on a higher‐order boundary element is applied to solve the resulting boundary‐value problems in the time domain. A recently developed new set of explicit time‐integration methods, which do not necessitate the use of upwind schemes for spatial derivatives, are adopted to deal with the convective‐type free‐surface conditions. To suppress the weak saw‐tooth instabilities on the free surface in time marching, we also present novel low‐pass filters based on optimized weighted least squares, which are in principle applicable for both structured and unstructured meshes. The presented schemes for the convection equation and the low‐pass filter are also relevant for other engineering fields dealing with similar mathematical problems. For ship seakeeping and added resistance analyses, we show that the present computational model does not need to use soft‐springs for surge and sway, in contrast to the traditional models. For a floating monopile, the importance of consistently taking into account the effects of large horizontal motions is demonstrated considering the bichromatic incident waves. The present model is considered as a complete second‐order wave‐load model, as all the second‐order wave loads, including the sum‐frequency and difference‐frequency components, are solved simultaneously.